Literature Learning with AI Support: A Case Study of Teaching the Novel of Laut Bercerita - Saraswati, Ekarini (Proceeding International Conference on Education, 2025)
This study seeks to investigate the function of artificial intelligence (AI) in fostering inclusive literary education, specifically through a case study of the teaching of Leila S. Chudori's novel Laut Bercerita. The novel explores issues of government violence, forced disappearances, and historical trauma within the framework of the New Order dictatorship. The novel's historical complexity and emotional depth require a pedagogical approach that accommodates the diverse linguistic, cultural, and psychological backgrounds of students. Using a descriptive qualitative methodology with a case study framework, data was collected through observation, comprehensive interviews, and digital documentation at two high schools that have adopted AI-based learning. This study employs three main theoretical frameworks: reader response theory, critical digital pedagogy, and trauma-informed education. Findings indicate that AI significantly contributes to five dimensions of learning: (1) eliminating linguistic barriers through automatic glossaries and contextual translation; (2) enhancing historical understanding through interactive media; (3) offering emotional support through trigger warning features and guided journals; (4) fostering inclusive discourse through anonymous participation; and (5) enabling locally informed interpretations shaped by students’ experiences. This research primarily contributes by providing an AI-based literary learning model that integrates critical and trauma-informed pedagogical strategies with digital technology. This study advocates for the integration of AI as an ethical and adaptive pedagogical ally in humanities education, emphasizing the need for teacher training and educational policies that acknowledge student diversity and the complexities of literary texts.